علاقة الصحة التنظيمية بسلوك الصمت التنظيمي - عكسه سمية; منصور بوبكر (University of Eloued جامعة الوادي, 2024)
هدفت هذه الدراسة الى التعرف على العلاقة بين الصحة التنظيمية والصمت التنظيمي لدى الموظفين الإداريين بجامعة الوادي ولتحقيق أهداف الدراسة تم تطبيق استبيان على عينة الدراسة التي بلغت 94 موظفا إداريا اختيرت بطريقة عشوائية وتم الاعتماد على المنهج الوصفي الارتباطي واستخدمت معامل الارتباط بيرسون لاختبار فرضيات الدراسة بالاعتماد على البرنامج الاحصائي spss25 وتوصلت نتائج الدراسة الى وجود علاقة ارتباطية طردية قوية للصحة التنظيمية على الصمت التنظيمي لدى الموظفين الإداريين بجامعة الوادي. Abstract: The main objective of this study is to identify the relationship between organizational health and organizational silence among administrative employees at the university of EL OUED .in order to achieve our objective a questionnaire was applied to a random sample of 94 administrative employees. We adopted a descriptive correlation analysis using the statistical software SPSS25, and the Pearson correlation coefficient was used to test the hypotheses, our main results show that there is a strong positive correlation between organizational health and organizational silence among administrative employees at the University of ELOUED.
دراسة ميدانية على عينة من الموظفين الإداريين بجامعة الوادي
Keywords: الصحة التنظيمية; الصمت التنظيمي; organizational health; organizational silence; administrative employees